Application of Tri Hita Karana (THK) in Harmonizing the Culture of the Hubula Community in Balim Valley - Gombo, Mikaus (Universitas Pahlawan Tuanku Tambusai, 2024)
This article examines the application of Tri Hita Karana (THK) in the culture of the Hubula community of Balim Valley, Papua Highlands, emphasizing harmonious values that parallel those in Balinese Hindu society. The Hubula people incorporate the THK concept—traditionally rooted in Balinese Hindu beliefs—into key aspects of their lives, particularly in rituals related to agriculture (wen), livestock (wam), and leadership or conflict resolution (wim/ab-kain). They believe in a triadic harmony among the Creator (Walkarige), humanity, and nature (o’birige mende), which also includes maintaining balanced relationships among people (ab-kumi inom). This qualitative study explores these relationships, finding that harmony between the Creator, nature, and human society is upheld through this adapted THK framework. Unlike the theological and philosophical approach common in Abrahamic religions, the Hubula community’s relationship with the Creator is material and practical, emphasizing an interconnected, tangible approach to spirituality and social values.